The Role of Emotional Intelligence and Empathy in Reducing Prejudice - Shehzad Khattak; Sobia Shah; Roshni; Hamad Saeed (Research Journal of Psychology, 2025)
Prejudice is a widespread problem that fuels social inequality, discrimination, and conflict, especially in culturally diverse regions like Khyber Pakhtunkhwa (KP), Pakistan. This study explores how emotional intelligence (EI) and empathy can help reduce prejudice among urban and rural populations in KP. EI, which involves recognizing and managing one’s emotions, and empathy, the ability to understand and share the feelings of others, are essential psychological tools in combating biases and promoting social harmony. The study gathered data from 300 participants, split equally between urban and rural areas, using reliable scales to measure EI, empathy, and prejudice. The findings revealed that higher levels of both EI and empathy were strongly linked to lower levels of prejudice. Urban participants showed higher emotional intelligence and empathy than those from rural areas. Empathy, in particular, was found to play a key role in mediating the relationship between EI and prejudice, emphasizing its importance in promoting inclusivity. These results highlight the need for targeted interventions aimed at boosting emotional intelligence and empathy, particularly in rural areas, to reduce prejudice. The study adds to our understanding of how psychological factors can bridge social divides and foster greater harmony in diverse communities.